COMMUNICATION MODEL ADAPTED TO THE ENTREPRENEURIAL CONTEXT OF THE CITY OF FIANARANTSOA MADAGASCAR - Andriamahazoarilala, S. J.; Razafindrakoto, L. S.; Rojosoanotahina, J. C.; Hajalalaina, A. R. (International Journal of Research -GRANTHAALAYAH, 2025)
Communication, defined as an interaction between two interlocutors, is an indispensable tool that human beings can not do without. Whether traditional or digital, it is necessary in education and in entrepreneurship. The obstacles relate to the communication systems of entrepreneurial support structures in the city of Fianarantsoa, Madagascar, particularly at the level of the models they have adopted. The objective of this research is therefore to study the communication systems of these structures. Different methods were adopted for data acquisition, such as analysis of the situation of existing structures by conducting an observation, an online opinion poll, a focus group, a survey and interviews within the various entrepreneurial support structures in the city and at the University of Fianarantsoa, Madagascar. This study is based on a sample of 302 individuals (mentors, startup owners, fokontany leaders, managers in the structures). After statistical analysis of the results, a hybrid communication model adapted to the contexts of these structures was proposed. As a perspective, this research can be extended to digital mapping of entrepreneurs in the use of digital technology and tools.